Nation and State - Abdullahi Abdulfatai Akanmu (Britain International for Academic Research (BIAR) Publisher, 2020)
This paper examines the nation and state with their features, merits, and demerits. The level of Nigeria as a nation-state is being appraised from the early of 1914 to 1963 and furthermore, examines the brief history of Nigerian politics from pre-1900-2020. The data collection is base on secondary data from the reliable sources such as textbooks, University lecture’s books and some other online sources. Therefore, this paper will promote high level of understanding among the students in the primary, secondary schools, higher institutions, and those in national-governmental positions in the various offices in order to differentiate between the level of nation and state, and how is it being measured in various sovereign states across the globe.